Evaluation of antioxidant potential of honey drops and honey lozenges - Petra Larsen; Marya Ahmed (Food Chemistry Advances, 2022)
The antioxidant potential of honey comes from various components including phenolic acids, enzymes (catalase, glucose oxidase), flavonoids, vitamins, organic acids, and Maillard reaction products that are nascently present in raw honey. Hence, it would be highly beneficial for consumers to develop honey-based candies such as honey drops and lozenges that can maintain health benefits of its precursors. This study is focused on evaluating the changes in chemical profiles of honey, specifically phenolic content and hydroxymethylfurfural (HMF) formation upon formulation of raw honey into honey lozenges and honey drops and evaluation of antioxidant properties of honey-based products using different antioxidant assays. Our results indicate that in comparison with raw honey, honey lozenges and drops contain higher total phenolic and HMF components, as well as exhibit greater antioxidant properties as is determined by multiple antioxidant assays.